Efektivitas Penggunaan AI Writing Tools (Grammarly & ChatGPT) dalam Pembelajaran Menulis Bahasa Inggris bagi Mahasiswa Produksi Ternak - P.A., Aisyah Nurdianingsih; Hawa Asma Ul Husna; Sa'diyah, Ilmatus (CV. ULIL ALBAB CORP, 2025)
This study investigates the effectiveness of AI Writing Tools spefically Grammarly and ChatGPT, in enhancing the academic writing skills of Animal Science students within the framework of English for Specific Purposes (ESP). Motivated by the persistent challenges faced by non-English major students in producing coherent and grammatically accurate texts, this quasi-experimental research involved two student groups: an experimental group using AI tools and a control group following conventional writing instruction. Data were collected through pre-tests and post-tests, followed by statistical analysis using paired and independent sample t-tests. The findings suggest that AI-based tools can serve as effective pedagogical aids, providing real-time feedback and structured guidance to support the writing process. Integrating such tools into ESP instruction not only improves linguistic accuracy but also encourages learner autonomy and engagement. The study recommends the incorporation of AI-assisted writing in ESP curricula and calls for further research into its application across other disciplines and writing genres.